2020
DOI: 10.1111/csp2.266
|View full text |Cite
|
Sign up to set email alerts
|

Potential feminization of Red Sea turtle hatchlings as indicated by in situ sand temperature profiles

Abstract: Climate change poses a serious threat to species that demonstrate temperature-dependent sex determination, including marine turtles. Increased temperatures can result in highly female-skewed sex ratios and decreased hatching success. The pivotal temperature that delineates hatchling sex ratios is commonly considered to be 29.2 C, but whether this threshold applies to turtles in the Red Sea region has not been tested in situ. For all species of marine turtles, there is a supposed thermal range of 25-33 C in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Hindcasting of sex ratios (1993−2018) gave approximately 73% female hatchling production and increasing to > 95% from 2075 to 2100 (Chatting et al 2021). Tanabe et al (2020) calculated the expected sex ratio of both green and hawksbill turtles in the Red Sea and showed that sites could already be exceeding thermal maximums and may be vulnerable to rising temperatures. On the contrary, findings from Pilcher at al.…”
Section: Threatsmentioning
confidence: 99%
“…Hindcasting of sex ratios (1993−2018) gave approximately 73% female hatchling production and increasing to > 95% from 2075 to 2100 (Chatting et al 2021). Tanabe et al (2020) calculated the expected sex ratio of both green and hawksbill turtles in the Red Sea and showed that sites could already be exceeding thermal maximums and may be vulnerable to rising temperatures. On the contrary, findings from Pilcher at al.…”
Section: Threatsmentioning
confidence: 99%
“…In 1989 the National Center for Wildlife (NCW) [formerly the National Commission for Wildlife Conservation and Development] initiated detailed studies of multiple aspects of the nesting turtles, including their morphology and their nesting success (Al-Merghani et al, 2000;Pilcher and Al-Merghani, 2000;Al-Mansi et al, 2003;Al-Mansi, 2016). In addition to studies concerning the turtles, physical characteristics of the beach and environmental factors were studied to determine their impact on the hatching success of eggs (Al-Mansi et al, 1991;Pilcher, 1999;Tanabe et al, 2020). Jensen et al (2019) defined a unique genetic allele from the green turtles nesting at Ras Baridi.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings highlight the shortage of information on sea turtle nesting throughout most of the Saudi Arabian Red Sea. This is not an unexpected result: Ras Baridi is the only well-studied nesting area in the region ( Miller, 1997 ; Pilcher, 1999 ; Pilcher & Al-Merghani, 2000 ; Tanabe et al, 2020 ; Shimada et al, 2021a ; Shimada et al, 2021b ; Al-Mansi et al, 2021 ). Expanding research efforts at other sites should be a priority in the face of rapid coastal development.…”
Section: Discussionmentioning
confidence: 80%
“…Dust from the nearby cement factory was also present, but in very small quantities, indicating that recent mitigation efforts to reduce beach contamination have been largely successful ( MEPA, 1983 ). We hypothesise that sediment composition at Ras Baridi could be responsible for the increased sand temperature at this site compared to other Red Sea nesting sites ( Tanabe et al, 2020 ) from increased sand albedo.…”
Section: Discussionmentioning
confidence: 84%